Rancang Bangun Purwarupa Simulasi Sistem Keamanan Rumah Berbasis Internet of Things: Design and Implement of IOT-based Home Security Simulation Prototype - Saputra, Muhammad Harpan Teguh; Arimbawa, I Wayan Agus; Wijaya, I Gede Pasek Suta (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
The use of information technology has spread to all fields, for example in the field of security using the Internet of Things technology. One of the places that need to be given security is the home, so that in this study prototypes of home security systems using the Internet of Things have been made with the aim of providing information to homeowners in the event of infiltration through windows or doors, gas leaks and fires. The tools used are Arduino Mega 2560 as a microcontroller, gas sensor, fire sensor, magnetic switch sensor, RFID, keypad, and selenoid. The home security system is made so that homeowners can control the condition of the home. The results of this study are that the home security systems that are made can run well and can be integrated with home security information systems. Sensors can detect gas leaks, fires, and doors or windows open when the security system is active. Homeowners can only turn off the home security system and unlock the door by using RFID tags that have registered IDs and correct passwords. Home security systems can also turn on alarms and send notifications to homeowners, fire stations and police stations in the event of a fire, gas leak or window or door that is opened when the security system is active.